Forecasting in the presence of structural breaks and model uncertainty - Rapach, David E.; Wohar, Mark E.; Beladi, Hamid; Choi, Kwang, 1947- (Frontiers of economics and globalization, 2008)
Forecasting in the presence of structural breaks and model uncertainty are active areas of recent research with crucial implications for practical problems in forecasting. Forecasting in the Presence of Structural Breaks and Model Uncertainty presents findings from the recent literature and new findings in a way that will be very useful to academic researchers and practitioners alike.Each chapter includes detailed empirical applications that demonstrate the usefulness (and limitations) of different methods for generating forecasts when structural breaks and model uncertainty are of significant concern. The authors describe in detail their methods and their results, and the data and programs are made available on a web site devoted to the book. The volume addresses forecasting variables from both Macroeconomics and Finance, and considers many different methods of dealing with model instability and model uncertainty when forming forecasts.Authors are leading experts in the topics they survey and extend. This book is supported by a website detailing the data and programs used.